Understanding Circular RNAs in Health, Welfare, and Productive Traits of Cattle, Goats, and Sheep - Dimitra Kirgiafini; Maria-Anna Kyrgiafini; Theocharis Gournaris; Zissis Mamuris (Animals, 2024)
Circular RNAs (circRNAs) are unique noncoding RNA molecules, notable for their covalent closed-loop structures, which play a crucial role in regulating gene expression across a variety of biological processes. This review comprehensively synthesizes the existing knowledge of circRNAs in three key livestock species: Bos taurus (cattle), Ovis aries (sheep), and Capra hircus (goats). It focuses on their functional importance and emerging potential as biomarkers for disease detection, stress response, and overall physiological health. Specifically, it delves into the expression and functionality of circRNAs in these species, paying special attention to traits critical to livestock productivity such as milk production, meat quality, muscle development, wool production, immune responses, etc. We also address the current challenges faced in circRNA research, including the need for standardized methodologies and broader studies. By providing insights into the molecular mechanisms regulated by circRNAs, this review underscores their scientific and economic relevance in the livestock industry. The potential of circRNAs to improve animal health management and the quality of animal-derived products aligns with growing consumer concerns for animal welfare and sustainability. Thus, this paper aims to guide future research directions while supporting the development of innovative strategies in livestock management and breeding.